2014
DOI: 10.1002/qua.24637
|View full text |Cite
|
Sign up to set email alerts
|

The chemical physics of unconventional superconductivity

Abstract: Attempts to explain correlated-electron superconductivity (SC) have largely focused on the proximity of the superconducting state to antiferromagnetism. Yet, there exist many correlated-electron systems that exhibit insulatorsuperconducting transitions where the insulating state exhibits spatial broken symmetry different from antiferromagnetism. Here, we focus on a subset of such compounds which are seemingly very different in which specific chemical stoichiometries play a distinct role, and small deviations f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The above results show that the PEC is a distinct phase in the correlated ρ = 1 2 systems and is actually observed in 2D CTS with CO. In analogy with the conjectures built around the concept of a density wave of Cooper pairs [43,44,[502][503][504][504][505][506][507], we have further proposed that SC will occur upon the destabilization of the PEC state [16,124,125,565,574]. Note that this idea also has overlaps with the idea of SC emerging from a 2D SP state (which we have emphasized does not exist at ρ = 1), as the dimerized horizontal stripes of Figs.…”
Section: Paired Electron Crystal In Two Dimensionssupporting
confidence: 57%
“…The above results show that the PEC is a distinct phase in the correlated ρ = 1 2 systems and is actually observed in 2D CTS with CO. In analogy with the conjectures built around the concept of a density wave of Cooper pairs [43,44,[502][503][504][504][505][506][507], we have further proposed that SC will occur upon the destabilization of the PEC state [16,124,125,565,574]. Note that this idea also has overlaps with the idea of SC emerging from a 2D SP state (which we have emphasized does not exist at ρ = 1), as the dimerized horizontal stripes of Figs.…”
Section: Paired Electron Crystal In Two Dimensionssupporting
confidence: 57%
“…Empirically, CTS showing the BCDW1 distortion are more likely to show superconductivity (SC) under pressure 4 . We have suggested that unconventional SC in ρ = 0.5 materials arises from the delocalization of the ('1−1') singlet pairs formed in the insulating Paired Electron Crystal (PEC), which has the same CO pattern • • • 1100 • • • as BCDW1 and BCDW2 [27][28][29] . Within such a model, the effective mass of the singlet is smaller in the BCDW1 because of the weaker binding, and hence the mobility of inter-dimer pairs here would be expected to be large, allowing a transition to a paired liquid state under the application of pressure 28 .…”
Section: B Bcdw1mentioning
confidence: 99%
“…Two of us have recently pointed out the unusual abundance 34 of seemingly unrelated correlated-electron materials that are superconducting at carrier concentration ρ 0.5. In all cases the superconductor belongs to a family of materials with varying ρ, and no SC is observed for ρ substantially different from 0.5 (as is also true for the CTS).…”
mentioning
confidence: 99%